Optimizing JMeter on Performance Testing Using the Bulk Data Method - Nurullah Husufa; Ifan Prihandi (Journal of Information System and Informatics, 2022)
Company X is one of the companies engaged in the telecommunications business. To improve customer service, the company developed an Application Programming Interface). The developed API is used to promote product packages to customers. Sending data via API to millions of customers at the same time, can lead to failures due to the inability of the server to process that data. JMeter is one of the tools that can be used to perform performance testing of an API by providing TPS calculation output. Bulk data files are used as input to process large amounts of customer data on JMeter. Proper thread properties settings affect the TPS value, and the study has managed to achieve the TPS value to be achieved with error rate = 0, which means success.